2018
DOI: 10.1007/s10006-018-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

To assess the efficacy of socket plug technique using platelet rich fibrin with or without the use of bone substitute in alveolar ridge preservation: a prospective randomised controlled study

Abstract: Atraumatic extraction may minimise the post-operative pain and discomfort to patient as well as the post-extraction alveolar height and width changes. The use of PRF and/or bone substitute even though clinically contributes to better post-operative healing and minimal loss of alveolar width and height, the values were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…On the contrary, a recent study showed no significant differences in terms of bone density and alveolar ridge dimensions for sockets treated with A‐PRF, FDBA or a combination of A‐PRF and FDBA (Clark, Rajendran, Paydar, Ho & Cox, ). Adding PRF to Plaster of Paris also did not return any significant benefit for ridge preservation (Girish Kumar, Chaudhary, Kumar, Arora & Kumar, ). When comparing PRF to β‐TCP with collagen in preserving the socket of single‐rooted teeth, similar outcomes were reported at 6 months (Das, Jhingran, et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a recent study showed no significant differences in terms of bone density and alveolar ridge dimensions for sockets treated with A‐PRF, FDBA or a combination of A‐PRF and FDBA (Clark, Rajendran, Paydar, Ho & Cox, ). Adding PRF to Plaster of Paris also did not return any significant benefit for ridge preservation (Girish Kumar, Chaudhary, Kumar, Arora & Kumar, ). When comparing PRF to β‐TCP with collagen in preserving the socket of single‐rooted teeth, similar outcomes were reported at 6 months (Das, Jhingran, et al.…”
Section: Resultsmentioning
confidence: 99%
“…Extraction sockets were carefully cleaned from any remains of granulation tissue. Flapless extractions were attempted, but if necessary flaps were elevated at the discretion of the Operator All regions Not reported Zhang et al [ 49 ] Parallel CCT 28 (14 females and 14 males) 14 14 34.6 Patients with upper and lower mandibular molars diagnosed as fractured tooth or could not be retained for other reasons Not reported All patients were treated with the non‑flap minimally invasive extraction technology Molars 3 months Kumar et al [ 43 ] RCT Parallel/Split 48 (not further specified) Not reported Not reported 44.4 Patients requiring tooth extraction Not reported All teeth were extracted atraumatically using periotomes and luxators without raising mucoperiosteal flap All regions Not reported Asmael et al [ 58 ] RCT split mouth 20 males 20 20 44.2 Smoker patient with multiple teeth extraction Not reported Extraction in atraumatic manner All regions Not reported Clark et al [ 39 ] Parallel RCT 45 enrolled 40 analyzed (22 females and 18 males) Test 1:10 Test2:10 Control1:10 Control2:10 58 Patients with single-rooted tooth requiring extraction and replacement with a dental implant supported restoration Teeth were excluded if they demonstrated a buccal dehiscence of more than 25% of the length of the tooth or presence of acute infection of endodontic origin Non-t...…”
Section: Resultsmentioning
confidence: 99%
“…The flap was raised in order to have good access to necrotic tissue as, well as to close the whole bony defect with soft tissues. It is worth mentioning that PRF can be applied together with other biomaterials, such as decalcified freeze-dried bone graft (DFDBA) or calcium sulfate to maintain the width of the bone ridge after tooth extraction [30,31,32]. In the presented case, it was decided not to use any bone substitute because of the risk of complications with soft tissue healing and, as a result, increased risk of infection and sequestration of the bone graft.…”
Section: Discussionmentioning
confidence: 99%